Trade in differentiated product, trading regimes and unemployment - Thomas Moutos (Fondazione Eni Enrico Mattei (FEEM), 1997)
One of the most important consequences of the transition in Central and Eastern Europe has been the dismantling of the Council for Mutual Economic Assistance (CMEA). It is argued in this paper that the abrupt loss of trading partners for the former CMEA countries and the Newly Independent States (NIS) of the former Soviet Union is responsible for the ensuing contraction of output and the emergence of unemployment. A model in which trade is conducted in vertically differentiated products is constructed with the implication that the dismantling of "clearing trade" arrangements among CMEA countries may make unemployment more than just a short-run phenomenon.
Keywords: 330; Internationale Wirtschaft; Internationale Wirtschaftsbeziehungen; Produktdifferenzierung; Arbeitslosigkeit; Theorie; Osteuropa